CURRENT ACCOUNTS, SAVINGS, AND TIME DEPOSITS TO OPERATING PROFIT: A COMPARATIVE STUDY ON INDONESIAN STATE-OWNED BANKS - Apriani Simatupang; Gladys T. Evidente (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
This study compares current accounts, savings, term deposits, and operating profit among state-owned banks during the Covid 19 pandemic. This study also compares the effect of current accounts, savings, and term deposits on the operating profit of state-owned banks. The research method used is a comparative study. The study results were that during the Covid 19 pandemic, the most significant amount of current accounts was at BMANDIRI; savings and term deposits at BBRI; and operating profit was at BMANDIRI. The lowest current accounts, savings, term deposits, and operating profit were in BBTN. Comparing current accounts, savings, and term deposits, BBNI does not significantly affect operating profit. At BBRI, BMANDIRI, and BBTN, demand deposits, savings, and term deposits have a significant influence. BBTN's current accounts and savings have a negative effect on its operating profit, while BBRI and BMANDIRI have a positive effect. Term deposits at BBRI, BMANDIRI, and BBTN positively influence operational reports. It can be concluded that during the Covid 19 pandemic in 2020, current accounts, savings, and term deposits significantly influenced operating profit.